Predicting type 2 diabetes risk before and after solid organ transplantation using polygenic scores in a Danish cohort - dos Santos, Quenia; Leung, Preston; Thorball, Christian W.; Ledergerber, Bruno; Fellay, Jacques; MacPherson, Cameron R.; Hornum, Mads; Terrones-Campos, Cynthia; Rasmussen, Allan; Gustafsson, Finn; Perch, Michael; Sørensen, Søren S.; et al. (Frontiers in Molecular Biosciences, 2023)
Type 2 diabetes mellitus (T2DM) can be multifactorial where both genetics and environmental factors play a role. We aimed to investigate the use of polygenic risk scores (PRS) in the prediction of pre-transplant T2DM and post-transplant diabetes mellitus (PTDM) among solid organ transplant (SOT) patients. Using non-genetic risk scores alone; and the combination with PRS, separate logistic regression models were built and compared using receiver operator curves. Patients were assessed pre-transplant and in three post-transplant periods: 0-45, 46-365 and >365 days. A higher PRS was significantly associated with increased odds of pre-transplant T2DM. However, no improvement was observed for pre-transplant T2DM prediction when comparing PRS combined with non-genetic risk scores to using non-genetic risk scores alone. This was also true for predictions of PTDM in all three post-transplant periods. This study demonstrated that polygenic risk was only associated with the risk of T2DM among SOT recipients prior to transplant and not for PTDM.Combining PRS with a clinical model of non-genetic risk scores did not significantly improve the predictive ability, indicating its limited clinical utility in identifying patients at high risk for T2DM before transplantation, suggesting that non-genetic or different genetic factors may contribute to PTDM.